In vitro and in vivo hemocompatibility assessment of ultrathin sulfobetaine polymer coatings for silicon-based implants. (August 2019) - Iqbal, Zohora; Kim, Steven; Moyer, Jarrett; Moses, Willieford; Abada, Emily; Wright, Nathan; Kim, Eun Jung; Park, Jaehyun; Fissell, William H; Vartanian, Shant; Roy, Shuvo
Highly uniform silicon nanopore membranes were developed for applications in implantable bioartificial organs. A robust, readily scalable, non-fouling surface coating is required to enhance silicon nanopore membrane hemocompatibility. However, the coating must be ultrathin to keep the nanopores from occluding. Recently, zwitterionic brush polymers have demonstrated significantly lower fouling under biological conditions. In this study, we explore ultrathin zwitterionic poly(sulfobetaine methacrylate) (pSBMA) surface coating at sub-5 nm thickness. Membrane hydraulic permeability was measured before and after surface modification of silicon nanopore membranes, and pores were found to be patent and in agreement with coating thickness measurements. Coating stability was analyzed under biological shear as well as under blood flow in vitro and in vivo. Following exposure to shear over 24 h, coatings were characterized via X-ray photoelectron spectroscopy, goniometry, and ellipsometry, and found to survive biological shear. In vitro blood experiments with fresh human blood as well as in vivo 7-day and 26-day implants in a porcine model demonstrate minimal platelet adhesion and activation with pSBMA surface modification compared to unmodified silicon exposed to fresh human blood in vitro. These results demonstrate that ultrathin pSBMA surface modification is a viable choice for application in blood contacting implants with critical nanoscale features.